Out to School; Out to the Workshop: The Meanings of Studying in Prison (Praxis Educativa, 2023)
We propose to analyze formal and non-formal education and the meanings attributed to them by the educational community of the Penitentiary Unit N°9 of the city of La Plata, Argentina, under the orbit of the Buenos Aires Penitentiary Service. We will focus on the area of Language and Literature in the course 1°D in the Secondary Education Center N°471 and in a literary workshop developed within the framework of the Literary Pavilions for Freedom Program in articulation with the Integral Program of Assistance and Treatment for Young Adults. Through participant observation and semi-structured interviews we inquired into the meanings acquired by formal and non-formal education for the actors involved since these modalities allow building different relationships with knowledge and generate different integration processes between teachers, students, managers and workshop participants, which have emotional and affective dimensions
Keywords: Formal Education - Non-formal Education - Prison - Language and Literature – Argentina